New species of the snake eels Echelus and Ophichthus (Anguilliformes: Ophichthidae) from Taiwan - Mccosker, John E.; Ho, Hsuan-Ching (Zootaxa, 2015)
Three new species of ophichthid eels, subfamily Ophichthinae, are described and illustrated from specimens collected at fish markets in Taiwan. Included are: Echelus polyspondylus sp. nov., which is unique in its vertebral number (172–183), dorsal-fin origin (behind gill openings), and coloration (anal-fin membrane black posteriorly); Ophichthus bicolor sp. nov., which is unique in its mean vertebral formula (18-64-158), dorsal-fin origin (well behind gill openings), dentition (teeth large and conical), and contrasting coloration (tan dorsally, white ventrally); and O. shaoi sp. nov., which is unique in its mean vertebral formula (11-69-159), and prominent lip barbels. A key to Taiwanese species of Echelus and Ophichthus is provided.